Comparison of Islamic Criminal Law and National Law Regarding the Criminal Act of Rape Against Minors - Eko Widiansyah; Alfi Syahri (Program Pascasarjana UIN Sumatera Utara Medan, 2022)
This study examines the comparison between Islamic criminal law and Indonesian national law regarding the crime of rape against minors, focusing on legal regulation, sanctions, and victim protection. The increasing number of sexual violence cases against children in Indonesia highlights a significant gap between existing legal frameworks and their practical implementation. Therefore, this research aims to analyze how both legal systems regulate such crimes, to identify their similarities and differences, and to assess the relevance of Islamic criminal law in strengthening national law. This research employs a normative-empirical legal approach by analyzing statutory regulations, Islamic legal sources (Qur'an, Hadith, and classical as well as contemporary fiqh), and secondary data from official reports and relevant scholarly studies. The data are analyzed qualitatively using descriptive and comparative methods. The findings reveal that Indonesian national law provides explicit and comprehensive regulations, including strict criminal sanctions and mechanisms for victim protection, such as restitution and rehabilitation. However, its implementation remains suboptimal due to structural and cultural challenges. In contrast, Islamic criminal law emphasizes the protection of human dignity and strictly punishes perpetrators while exempting victims from liability, incorporating both punitive and restorative elements. In conclusion, both legal systems recognize rape against minors as a serious crime, yet differ in their legal construction and application. Islamic legal principles, particularly maqashid al-shari'ah, offer significant contributions in enhancing a more just, victim-oriented, and holistic legal framework within the national system.